2022
DOI: 10.3390/healthcare10030566
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine in Acute Brain Injury: Current Opinion Following Cerebral Circulation and Electrical Activity

Abstract: The use of ketamine in patients with TBI has often been argued due to its possible deleterious effects on cerebral circulation and perfusion. Early studies suggested that ketamine could increase intracranial pressure, decreasing cerebral perfusion pressure and thereby reducing oxygen supply to the damaged cerebral cortex. Some recent studies have refuted these conclusions relating to the role of ketamine, especially in patients with TBI, showing that ketamine should be the first-choice drug in this type of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Instead, ketamine can prevent indirectly acidosis because acts both as sedative and good inotropic on trauma, but its effect is very unclear in trauma induced coagulopathy. If on the one hand some studies demonstrate an inhibitory activity on platelets on the other hand it is an excellent drug for maintaining good hemodynamics and indirectly avoiding acidosis which in turn inhibits platelet function [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, ketamine can prevent indirectly acidosis because acts both as sedative and good inotropic on trauma, but its effect is very unclear in trauma induced coagulopathy. If on the one hand some studies demonstrate an inhibitory activity on platelets on the other hand it is an excellent drug for maintaining good hemodynamics and indirectly avoiding acidosis which in turn inhibits platelet function [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine is a non-opioid analgesic that has been administered in the clinic for decades. This drug is a strong analgesic and affects the sympathetic nervous system, which can benefit trauma patients [ 40 ]. For instance, ketamine increases the average heart rate and blood pressure, which are both favorable for stabilizing the trauma patient’s condition [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The regional analgesia provided through an epidural or brachial catheter should be considered for all trauma patients; this approach can, potentially, spare the use of systemic opioids and facilitate early mobilization. Epidural analgesia has been shown to produce high levels of patient satisfaction and improve lung function after thoracoabdominal and major orthopedic surgery in elective populations [ 40 ]. We retrieve similar benefits in trauma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has demonstrated that ketamine produces a state of sedation, analgesia, amnesia, retains the patient's respiratory drive and maintains the blood pressure. 11,12 A clinical trial reported better acceptance along with rapid onset and recovery along with fewer adverse effects when intranasal atomised ketamine (6 mg kg À1 ) was administered for dental procedural sedation as compared to nasal drops (6 mg kg À1 ). 13 Given its favourable sedative and anxiolytic properties, there is growing interest in the use of dexmedetomidine especially in the paediatric neurosurgical population on account of its minimal effect on respiratory rate and tidal volume.…”
Section: Introductionmentioning
confidence: 99%